Impact of perceived social support on psychological resilience: a comparison between medical and surgical postgraduate residents - Amreen; Anosha Arshad; Kanza Majid; Mishall Baig Ahmed; Sarah Misbah (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the predictable relationship and differences between perceived social support and psychological resilience among medical and surgical postgraduate residents. Method: The analytical cross-sectional study was conducted from July to September 2021 at Dr Ruth K.M. Pfau Civil Hospital, Karachi, and comprised postgraduate medical and surgical residents of either gender. Data was collected using validated self-administered questionnaires. Data was analysed using SPSS 22. Results: Of the 200 residents, 100(50%) were medical residents and 100(50%) were surgery residents. Besides, 161 (80.5%) were females and 39(19.5%) were males. The overall mean age was 27.57+2.13 years. Mean perceive social support score was 62.53+15.41 and mean score for psychological resilience was 70.40+13.73. Perceived social support was a significant predictor of resilience (p=0.0001). Medical residents scored significantly higher (p=0.034) on perceived social support compared to residents from surgery departments. Marital status, residency year, and birth order in the family significantly differed with reference to perceived social support and resilience (p<0.05). Conclusion: There was a favourable role of perceived social support in building resilience among postgraduate residents. Key Words: Social support, Psychological resilience, Internship and residents, Teaching hospital.